Love, Attachment, and Effacement: Romantic Dimensions in Sylvia Plath’s Children Poems - Wierzchowska, Justyna (International Journal of English Studies, 2018)
This article examines seventeen children poems by Sylvia Plath written in the years 1960-63, in relation to the poetics of romantic love. Drawing on motherhood studies (Klein, 1975; O’Reilly, 2010; Rich, 1976; Winnicott, 1956, 1965, 1967), the maternal shift in psychoanalysis (see Bueskens, 2014: 3-6), and attachment theory (Bowlby, 1950, 1969, 1988), it reads love as a continuous human disposition, informed by one’s attachment history, and realized at different stages of one’s life (Hazan & Shaver, 1987). It specifically refers to Daniel Stern’s and Anthony Giddens’s largely overlapping concepts of maternal and romantic love to argue that Plath’s children poems are significantly infused with a poetics of romantic love. This poetics, however, becomes gradually compromised by a poetics of ambivalence, withdrawal, and self-effacement.